Bank Accounting Conservatism and Bank Loan Pricing - LIM, Chu Yeong (Institutional Knowledge at Singapore Management University, 2014)
This paper studies the effects of bank accounting conservatism on the pricing of syndicated bank loans. We provide evidence that banks timelier in loss recognition charge higher spreads. We go onto consider what happens to the relationship between spreads and timeliness in loss recognition during the financial crisis. During the crisis, banks timelier in loss recognition increase their spreads to a lesser extent than banks less timely in loss recognition. These findings are broadly consistent with the argument that conditional accounting conservatism serves a governance role. The policy implication is that banks timelier in loss recognition exhibit more prudent and less pro-cyclical loan pricing behaviour.